TPACK-Based Digital Flipbooks to Reduce Misconceptions in Newton's Second Law Materials - Nur Aini Agustina; A Halim; Ibnu Khaldun; Agus Wahyuni; Elmi Mahzum; Ngadimin Ngadimin; Putri Nabilah (Jurnal Pemberdayaan Masyarakat, 2026)
Misconceptions concerning Newton’s Second Law remain prevalent among secondary school students and hinder meaningful physics learning. This study aimed to develop and evaluate a Technological Pedagogical and Content Knowledge (TPACK)-based digital flipbook designed to improve conceptual understanding and reduce misconceptions. The study employed a research and development approach using the 4D model (Define, Design, Develop, and Disseminate). Product feasibility was assessed through expert validation, while practicality was examined through limited field trials. Effectiveness was evaluated using a quasi-experimental non-equivalent control group design involving 60 eleventh-grade science students. Data were collected using validation instruments, student response questionnaires, and a four-tier diagnostic test administered as a pretest and posttest. The digital flipbook achieved a high feasibility score (89.51%) and demonstrated increased practicality after revision (from 57.13% to 89.27%). The experimental group showed substantially higher conceptual understanding (64.76%) and lower misconceptions (5.71%) compared to the control group (17.14% understanding; 27.86% misconceptions). Normalized N-Gain analysis indicated medium-to-high improvement in the experimental group, and an independent sample t-test revealed a significant difference between groups (t = 12.572; p 0.001). These findings indicate that the TPACK-based digital flipbook is feasible, practical, and effective, contributing an evidence-based instructional model for reducing physics misconceptions through integrated technology-enhanced learning.